First records of diurnal and nocturnal predatory birds from artificial hunting perch trials in oil palm plantations - Kamil Tohiran; Dzulhelmi Muhammad Nasir; Maisarah Burhanuddin; Frisco Nobilly; Raja Zulkifli; Ramle Moslim; Muhammad Syafiq Yahya; Ahmad Razi Norhisham; Alex M. Lechner; Badrul Azhar (BioControl, 2024)

Improvement of the entomopathogenic fungus Cordyceps javanica efficacy against Diaphorina citri (Hemiptera: Liviidae) under ultraviolet-B radiation and lower relative air humidity provided by oil formulations - Marcos R. Conceschi; Natasha Sant´Anna Iwanicki; Rafael de Andrade Moral; Celeste P. D’Alessandro; Italo Delalibera Junior (BioControl, 2024)

Potential biological control agents of Geosmithia morbida restrict fungal pathogen growth via mycoparasitism and antibiosis - Aaron J. Onufrak; Romina Gazis; Kimberly Gwinn; William Klingeman; Sima Khodaei; Luis I. Perez Oñate; Autumn Finnell; Spencer Givens; Cristine Chen; David R. Holdridge; Denita Hadziabdic (BioControl, 2024)
Thousand cankers disease of Juglans (walnut) and Pterocarya (wingnut) spp. (Fagales: Juglandaceae) is caused by the fungal pathogen Geosmithia morbida Kolarík, Freeland, Utley, and Tisserat (Hypocreales: Bionectriaceae) and bark beetle pest/vector, Pityophthorus juglandis Blackman (Coleoptera: Curculionidae). To further the development of biological management strategies for thousand cankers disease, we assessed the ability of 14 endophytic Trichoderma (Hypocreales: Hypocreaceae) isolates and the commercially available isolate T. afroharzianum strain KRL-AG2 to inhibit the in vitro growth of three different G. morbida isolates via mycoparasitism and antibiosis. To identify factors that may affect field success of candidate biological control agents, we quantified the growth responses of Trichoderma spp. and the commercially available entomopathogenic fungus, Beauveria bassiana (Bals.-Criv.) Vuill. (Hypocreales: Cordycipitaceae) strain GHA, to the plant secondary metabolite and antimicrobial compound, juglone in vitro. A total of 12 Trichoderma isolates (from six different Trichoderma species) demonstrated antagonistic activity towards G. morbida in dual-plate assays. Juglone consistently reduced the growth of B. bassiana strain GHA and 14 of the 15 screened Trichoderma isolates in vitro. Additionally, one metabolite-producing Trichoderma isolate, TN4-47, completely inhibited the growth of all three G. morbida isolates across all tested metabolite concentrations and had comparatively greater tolerance to juglone compared to other Trichoderma isolates. Future lines of research should focus on characterizing the active antagonistic compound present in the metabolite filtrates, determine the mode of action of the active component(s), and elucidate how abiotic and biotic factors may influence the growth, persistence, and antagonistic activity of candidate biological control agents in planta .

Life cycle, host specificity and potential impact of a gall-inducing thrips Acaciothrips ebneri, a biological control agent for prickly acacia (Vachellia nilotica subsp. indica) in Australia - Boyang Shi; Kunjithapatham Dhileepan (BioControl, 2024)
Prickly acacia ( Vachellia nilotica subsp. indica (Benth.) Kyal. & Boatwr.; Fabales: Fabaceae) is a Weed of National Significance and a target for biological control in Australia. Currently there are no effective biological control agents for the weed in Australia. Based on genetic and climate matching, a gall thrips ( Acaciothrips ebneri Karny; Thysanoptera: Phlaeothripidae) inducing rosette galls resulting in shoot tip dieback, was identified as a prospective biological control agent from Ethiopia. No-choice host-specificity tests were conducted on 59 test plant species in a high security quarantine in Brisbane, Australia. Acaciothrips ebneri is host-specific, inducing galls and reproducing only on prickly acacia. Acaciothrips ebneri , as predicted by the CLIMEX model, is suited to hot and arid western Queensland where major prickly acacia infestations occur. The Australian Government approved A. ebneri for field release in October 2022. This is the first time a true gall-inducing thrips has ever been approved as a weed biological control agent. Field releases commenced in January 2023 and are in progress. There are early signs of field establishment resulting in shoot tip die back in the field, and field release and monitoring will continue.

Dusting Metarhizium rileyi conidia with a drone for controlling fall armyworm and soybean looper in maize and soybean fields - Rogerio Biaggioni Lopes; Fernando Garcia Nicodemos; Ana Beatriz Zacaroni; Hebert Ribeiro de Souza; Marcos Faria (BioControl, 2024)

Host preference and mortality caused by the parasitoid Sclerodermus guani on different cerambycid species - Qun Yu; Shuang Li; Yu-Jun Kong; Zuo-Xiang Sun; Dan-Dan Cao; Jian-Rong Wei (BioControl, 2024)

Within-host competition between Cotesia flavipes and Heterorhabditis bacteriophora in Diatraea saccharalis - Telliane Santos Salgueiro Silva; Patricia da Silva Santos; Rayanne Ingrid Silva Vieira; Aldomário Santo Negrisoli Junior; Elio Cesar Guzzo (BioControl, 2024)

Effects of mealybug and female body sizes on host examination and offspring developmental performances in the gregarious hyperparasitoid Cheiloneurus nankingensis - Wenquan Qin; Tingting Yao; Ling Meng; Baoping Li (BioControl, 2024)

Biocontrol of Fusarium spp. root rot in yerba mate (Ilex paraguariensis) by native rhizospheric Trichoderma spp. - Alexsandra Cezimbra Quevedo; Marlove Fátima Brião Muniz; Janaina Silva Sarzi; Jaqueline Raquel Tomm Krahn; Lucas Graciolli Savian; Luciane Almeri Tabaldi; Marisa Ana Strahl; Mateus Alves Saldanha; Ricardo Harakava; Tales Poletto; Júlio Carlos Pereira da Silva (BioControl, 2024)

How plant and insect host characteristics affect pepper weevil Anthonomus eugenii parasitism efficacy by the pteromalid Jaliscoa hunteri - Serena Leo; Roselyne Labbé; Cynthia Scott-Dupree (BioControl, 2024)
The pepper weevil Anthonomus eugenii (Cano) (Coleoptera: Curculionidae) is an economically important pest of both field and greenhouse pepper crops, Capsicum annuum Linnaeus (Solanaceae) in North America. Among its natural enemies is the parasitoid wasp Jaliscoa (= Catolaccus ) hunteri (Crawford) (Hymenoptera: Pteromalidae), whose potential control of A. eugenii appears promising but is currently unclear. We conducted controlled environment trials to quantify A. eugenii offspring emergence following exposure to J. hunteri , examining how parasitoid exposure period, weevil host life stage, pepper cultivar, fruit size and abscission status affect weevil-natural enemy dynamics. In pepper cultivar comparison trials, we identified a significant reduction in weevil offspring emergence from three different cultivars of ornamental peppers infested by A. eugenii , but no difference among them. In trials comparing wasp exposure period and weevil larval instar, pepper plants of one cultivar (Blaze) were exposed to A. eugenii adults, and subsequently to J. hunteri wasps for either three or seven days, when offspring weevils were either at the L1 or L3 instar. Offspring emergence was significantly reduced up to 62% when L3 but not L1 weevils were exposed to wasps for 7 days. Following this longer exposure period, significantly greater weevil suppression occurred in small (71.7%) versus large fruit (62.5%), with an additional 15.1% weevil suppression resulting from attached relative to abscised fruit. These results highlight the potential for J. hunteri as a biological control agent of A. eugenii on pepper crops, with particular value in commercial greenhouse production where wasp retention rates can be high.

Tachinids in conservation biological control of phytophagous Pentatomidae - Celina Andrea Fernández; Eduardo Lujan Punschke; M. Fernanda Cingolani; Ana Paula Carrizo; M. Candela Barakat; Rodrigo de Vilhena Perez Dios; Franco Blengino; Facundo Huarte; Guillermo Alberto Montero (BioControl, 2024)

Conservation biological control of stink bugs: current knowledge and future perspectives - María Fernanda Cingolani; Raúl Alberto Laumann (BioControl, 2024)

Does intraspecific variation in Trissolcus japonicus affect its response to non-target hosts? - Nina Häner; Fleur Fenijn; Tim Haye (BioControl, 2024)
Host specificity is a key criterion for the implementation of any biological control program. In parasitoid wasps, host specificity is mediated by their response to chemical cues directly and indirectly associated with their hosts during foraging. Although intraspecific variation in foraging behaviour is documented, it is rarely integrated into risk assessment studies of potential biological control agents, as is the case for Trissolcus japonicus (Ashmead) (Hymenoptera: Scelionidae), an Asian egg parasitoid and biological control agent of the invasive Halyomorpha halys (Stål) (Hemiptera: Pentatomidae). In the present study, we compared the behavioural response of T. japonicus females of an adventive line present in Switzerland and an Asian line (Beijing USDA), recently mass released in Italy, to cues of its target host H. halys and non-target host Pentatoma rufipes (L.) (Hemiptera: Pentatomidae). We observed minimal differences in host acceptance, exploitation and suitability in no-choice tests. In contrast, the behavioural response to host contact kairomones left on leaf substrates significantly differed between the two lines. While both lines preferred chemical footprints of H. halys in comparison to P. rufipes , females of the Beijing USDA line responded more strongly to host kairomones. The observed intraspecific variation in behavioural traits highlights the relevance of considering genetically distinct parasitoid lines and their host foraging behaviour in biological risk assessment studies. However, the implications of intraspecific variation in parasitoid foraging behaviour for biological control of a pest and non-target effects in the field remain challenging to predict.

Influence of the management of rice crops and wild vegetation on the diversity of Scelionidae egg parasitoids of Pentatomidae - Simone Mundstock Jahnke; Gisele de Souza da Silva; Norman F. Johnson (BioControl, 2024)

Chemical and visual stimuli for conservation biological control of stink bugs in soybean: potential use and flaws on egg parasitoid recruitment - Ana Carolina G. Lagôa; Pedro H. B. Togni; Michely F. Aquino; Maria Carolina Blassioli-Moraes; Miguel Borges; Raúl A. Laumann (BioControl, 2024)

Management of Euschistus heros with the release of Telenomus podisi in soybean in Brazil - Gabryele Silva Ramos; Alessandro Bandeira Dalbianco; Daniel Mariano Santos; Daniel de Lima Alvarez; Regiane Cristina de Oliveira (BioControl, 2024)

The indirect effect of nectar-inhabiting yeasts on olfactory responses and longevity of two stink bug egg parasitoids - Jay Darryl L. Ermio; Ezio Peri; Patrizia Bella; Michael Rostás; Islam S. Sobhy; Tom Wenseleers; Stefano Colazza; Bart Lievens; Antonino Cusumano (BioControl, 2024)
Adult parasitoids are well known to feed on sugar-rich resources such as floral nectar. Recently, an increasing body of evidence has shown that nectar is ubiquitously colonized by microorganisms and, as a consequence, microbial metabolic activity can affect several traits of floral nectar. Yet, how the fermentation of nectar by yeasts impacts the olfactory responses and performance of parasitoids is largely understudied, especially in the case of egg parasitoids. In this study, we investigated whether fermentation by the nectar yeasts Metschnikowia gruessii and M. reukaufii affects the olfactory responses of Trissolcus basalis and Ooencyrtus telenomicida, two egg parasitoid species associated with the southern green stink bug Nezara viridula . We also investigated how yeast fermentation affects the longevity and survival of the egg parasitoids. Results of static four-chamber olfactometer tests showed that nectar fermented by M. gruessii (but not by M. reukaufii ) was attractive to both egg parasitoid species, whereas no significant yeast-mediated effects were found in terms of wasp longevity. Gas chromatography coupled with mass spectrometry (GC-MS) showed a clear separation of the volatile profiles among M. gruessii , M. reukaufii and non-fermented control nectar supporting the results of the insect bioassays. The results of our study highlight the need to consider the role of microbes when studying interactions between flower nectar and egg parasitoids and could have implications from a conservation biological control perspective.

Influence of landscape structure on stink bug and their adult parasitoid populations on soybean culture - Michely Ferreira Santos de Aquino; Edison Ryoiti Sujii; Sérgio Eustáquio de Noronha; Miguel Borges; Maria Carolina Blassioli-Moraes; Raul Alberto Laumann (BioControl, 2024)

Life history studies of stink bugs: much-needed research to support their conservation biological control - Antônio Ricardo Panizzi; Tiago Lucini (BioControl, 2024)

Correction to: Predatory behavior and potentiality of Toxorhynchites spp. (Diptera: Culicidae) against Aedes mosquito - Punya Ram Sukupayo; Ram Chandra Poudel; Tirth Raj Ghimire (BioControl, 2024)

The effect of bioC gene on ultraviolet radiation and oxidative resistance of Bacillus thuringiensis (Bacillales: Bacillaceae) - Yile Zhang; Caixia Chen; Xi Du; Haonan Wu; Chunmei Chen; Hong Chen; Zhen Yu; Qingqing Min; Xiaohua Hu; Zhaoxia Liu; Weilong Tan; Xiong Guan; et al. (BioControl, 2024)

Endophytic Beauveria bassiana in sugarcane and associated Eldana saccharina host plants in South Africa - Nongcebo S. Memela; R. Stuart Rutherford; Stefan Schmidt (BioControl, 2024)
Eldana saccharina Walker is a problematic sugarcane stalk borer pest in South Africa. Twenty-eight sugarcane genotypes ( Saccharum spp. hybrids) and seven different species of host plants of E. saccharina were surveyed for the presence of endophytic Beauveria bassiana sensu lato ( s.l. ). Collectively, 326 plant samples (roots, stems, or leaves) were collected from five locations in sugarcane-producing areas (KwaZulu-Natal; South Africa). Following plant surface disinfection, 128 fungal colonies morphologically resembling Beauveria spp. were isolated from internal plant tissues. The sequence analysis of the internal transcribed spacer region confirmed that 13 representative isolates were B. bassiana. s.l . Eight B. bassiana isolates were recovered from E. saccharina natural host plants, and 120 from different sugarcane stem parts (top node, top internodes, bottom node, and bottom internode). Endophytic B. bassiana isolates were recovered from 22 of 28 sugarcane genotypes surveyed. The number of B. bassiana isolates obtained from different sugarcane parts differed significantly, with more B. bassiana isolates obtained from the top than the bottom internodes. Furthermore, sugarcane genotypes N31 and N41 yielded B. bassiana from all plant parts sampled, while five sugarcane genotypes harbored no B. bassiana isolates. This study demonstrates for the first time the natural occurrence of endophytic B. bassiana strains in sugarcane plants and E. saccharina host plants in South Africa.

Predatory behavior and potentiality of Toxorhynchites spp. (Diptera: Culicidae) against Aedes mosquito - Punya Ram Sukupayo; Ram Chandra Poudel; Tirth Raj Ghimire (BioControl, 2024)

Comparative efficacies of two fungal insecticides in field control of cereal aphids heavily infesting winter wheat - Sen-Miao Tong; Dan-Yi Qi; Chun-Ling Liu; Guan-Hua Feng; Wen-Yue Pan; Yan-Zhi Shao; R. Yang; Ming-Guang Feng (BioControl, 2024)

Beauveria bassiana (Ascomycota: Hypocreales) spores carried by Scleroderma guani (Hymenoptera: Bethylidae): a novel strategy for improving the control efficiency of Semanotus bifasciatus (Coleoptera: Cerambycidae) in the field - Jian-Yong Zeng; Jia-Wei Bai; Hua-Ling Wang; Xiao-Yu Su; Xue-Fei Wang; Ning-Ning Fu; Hui-Ping Li (BioControl, 2024)

Vertebrates and flying insects provide biocontrol services to Australian urban food gardens - Robert McDougall; Paul Kristiansen; Tanya Latty; Romina Rader (BioControl, 2024)
Biocontrol by wild insects and other organisms is an important service provided to agriculture, but few studies have linked the role of this service to urban garden crop production. In 15 urban food gardens in Sydney, Australia, we assessed predation and parasitism of two sentinel prey species, recorded pest control activities undertaken by gardeners and the produce yielded by garden crops. We observed substantial removal of sentinel prey (mean removal 22% for Tenebrio molitor larvae and 59% for Helicoverpa armigera ) but no parasitism. Vertebrate predators primarily consisted of urban adapted birds and mammals common throughout Australian cities. We measured a range of local and landscape scale environmental variables including plant richness and abundance, light, canopy cover, building density and distance to remnant vegetation. We found that gardeners undertook only basic pest control activities with little chemical use, yet high amounts of produce were harvested. Pest control services were poorly explained by environmental variables. Low active pest control activities, and high predation rates suggest pests are either well controlled or in low numbers in the surveyed urban food gardens. Given the vertebrate predators were generalist birds and mammals common to many parts of urban Australia, the provision of predation services to urban gardens by these taxa could be widespread across the continent.

Climate modelling of the potential distribution in South Africa of two Zygogramma species (Coleoptera: Chrysomelidae) released for the biological control of invasive weed Tithonia rotundifolia (Asteraceae: Heliantheae) - Khethani V. Mawela; David O. Simelane; Terence Olckers (BioControl, 2024)
Two Mexican leaf-feeding beetles, Zygogramma piceicollis (Stål) and Zygogramma signatipennis (Stål) (Coleoptera: Chrysomelidae), were released in South Africa for the biological control of the invasive species Tithonia rotundifolia (Mill.) S.E. Blake (Asteraceae: Heliantheae). The aim of this study was to predict the potential of these beetles to establish and spread in South Africa, using MaxEnt climate modelling that incorporated locality data recorded in Mexico between 2008 and 2019 and data from the Global Biodiversity Information Facility. Zygogramma signatipennis displayed a wider distribution than Z. piceicollis in Mexico, with some overlap between the two species. The average receiver operating characteristic curves obtained for Z. piceicollis and Z. signatipennis predicted high mean area under curve values of 0.910 and 0.885, respectively. Jackknife tests revealed that mean annual temperature had the highest gain when used in isolation for Z. piceicollis , compared with minimum precipitation of the driest month for Z. signatipennis . These tests also revealed that the highest and lowest contributing environmental variables for Z. piceicollis and Z. signatipennis were minimum precipitation of the driest month (37.9 and 46.7%) and maximum annual temperature of the warmest month (3.8 and 12.3%), respectively. MaxEnt modelling predicted that at least six of South Africa’s nine provinces provide regions that would support the proliferation of both beetles, with conditions best suited for Z. piceicollis . Despite predictions that both beetles should establish throughout the range of T. rotundifolia in South Africa, their realized establishment has so far been poor. Other factors, besides climate, including release size, site destructions, drought, soil moisture and texture could be constraining establishment.

Effects of Beauveria bassiana on the growth and reproductive rates of Nezara viridula - Maribel Portilla; Moukaram Tertuliano; Katherine Parys; James P. Glover; Gadi V. P. Reddy (BioControl, 2024)

Submersed herbicides and thrips biological control effectively reduce biomass of alligatorweed (Alternanthera philoxeroides), a widespread aquatic invasive plant - Samuel A. Schmid; Gray Turnage; Gary N. Ervin (BioControl, 2024)

Benefits associated with the implementation of biological control programmes in Latin America - Yelitza C. Colmenarez; Carlos Vasquez (BioControl, 2024)
Agriculture in Latin America plays a significant role in the region’s economy, food security, and rural development. Although pest control has traditionally relied on chemicals, there is increasing adoption of sustainable agricultural practices. Thus, in recent years, there has been a growing emphasis on sustainable agriculture practices, including biological control, to minimise environmental impact, conserve natural resources, and ensure long-term agricultural productivity. In Latin America, high biodiversity enhances biological control, both classical and augmentative biological control. The use of biological control agents allows farmers to produce their crops whilst reducing the use of chemicals in agriculture. In addition, biological control opens new market opportunities for farmers and job options for youth in rural areas. Maximal benefits will however be attained only after adoption of biological control practices and when an effective interaction among key stakeholders is achieved. Thus, farmers and consumers can reap the benefits of biological control, which can incentivise and accelerate adoption at the field level. To evaluate the socio-economic benefits of biological control, establishing multidisciplinary teams to conduct the studies is crucial. The current article explores the benefits resulting from the implementation of biological control programmes, highlighting social benefits. In addition, as part of the Plantwise programme, created to assist agricultural production with a sustainable perspective, data on the use of biopesticides in some countries are discussed in the context of sustainable production looking forward to reinforcing food security and safety in Latin America.

A growing number of benefit evaluations and new innovations should foster broader adoption of classical biological control - Mark Schwarzländer; Peter G. Mason (BioControl, 2024)

Studies on the host selection of a weed biological control candidate facilitate pre-release environmental safety assessments - Bijay Subedi; Mark Schwarzländer; Sanford D. Eigenbrode; Bradley L. Harmon; Philip Weyl (BioControl, 2024)
Pre-release host specificity testing can reliably predict the environmental safety of weed biological control agent (BCA) candidates but typically does not consider their host-finding behavior. Therefore, BCA candidates that do not utilize non-target plants in the field post-release, despite development on such plants in pre-release tests, may be prematurely disqualified for release. We addressed this issue with the seedpod weevil Ceutorhynchus peyerimhoffi , a BCA candidate for the invasive Eurasian mustard Isatis tinctoria . Ceutorhynchus peyerimhoffi weevils, both naive and experienced, were tested for their responses to olfactory, visual, and combined olfactory and visual cues of Braya alpina , Caulanthus heterophyllus , and the US federally listed Boechera hoffmannii . These responses were compared to I. tinctoria or control treatments in a modified Y-tube olfactometer set-up. Naïve and weevils with prior experience on I. tinctoria responded with attraction to olfactory, visual, and combined cues of I. tinctoria . In contrast, there was no attraction by either naïve or experienced weevils to non-target plant cues, except for attraction to C. heterophyllus combined cues by experienced weevils. Furthermore, visual cues of B. alpina and B. hoffmannii were repellent to experienced weevils, and olfactory cues of B. alpina were repellent to naïve weevils. We conclude that C. peyerimhoffi uses visual and olfactory cues to discriminate between its host plant I. tinctoria and North American non-targets. Behavioral host selection studies involving multimodal cues can provide a mechanistic explanation of host selection and complement environmental safety assessments of weed BCA candidates.

Using economics to inform and evaluate biological control programs: opportunities, challenges, and recommendations for future research - Katherine Lee; Shana McDermott; Linda Fernandez (BioControl, 2024)
Assessing the economics of biological controls in pest and invasive species control is pivotal for guiding research and decision making. The field of economics provides numerous systematic methods to assess the impacts and values created by biocontrol programs, as well as weigh the trade-offs of allocating resources to research, development, and management activities. This article discusses economic methods used to evaluate the impacts and quantify the net benefits of biological control programs, including data needs and shortcomings of methodologies. We cite examples from the literature on the economics of biological control to provide insight into the various ways in which economics contributes to the design, evaluation, and development of recommendations for biological control programs. We then discuss general trends and highlight knowledge gaps, providing suggestions for enhancing the use of economics in the analysis of biological control programs in the existing literature. This article is intended to serve as resource for researchers and policymakers interested in assessing benefits and trade-offs of biological control programs through the lens of economics.

Traits of insect herbivores and target weeds associated with greater biological weed control establishment and impact - Sujan Panta; Mark Schwarzländer; Philip S. R. Weyl; Hariet L. Hinz; Rachel L. Winston; Sanford D. Eigenbrode; Bradley L. Harmon; Sven Bacher; Quentin Paynter (BioControl, 2024)
Improving success rates of classical weed biocontrol programs is an ongoing effort that requires a variety of different approaches. Previous assessments indicated biocontrol agent taxonomy and feeding characteristics and weed life history traits are associated with better control outcomes. We examined weed biocontrol releases for correlations between biocontrol agent and target weed traits associated with different levels of reported establishment and control. Data collated in the 5th edition of ‘Biological Control of Weeds: A World Catalogue of Agents and Their Target Weeds’ were used as the basis for this global analysis. Published literature was used to augment the catalog with data for eight biocontrol agent traits and four target weed traits. Biocontrol agent establishment and impact data were analyzed against these traits using generalized linear mixed models and categorical models, respectively. Analyses for biocontrol agent establishment reveal the following agent traits were correlated with a greater probability of establishment: being an internal feeder, feeding on above-ground plant tissues, multivoltine agents and agents that feed during both their adult and immature life stages. Insect taxon did not affect establishment except for the order Lepidoptera, which had the lowest establishment probability. For weed traits, those occurring in aquatic or riparian habitats were associated with a higher probability of biocontrol agent establishment. Regarding agent impact, using the definition categories in the catalog, agents feeding externally and on vegetative plant tissues, multivoltine agents and those with both adult and immature plant-feeding life stages were strongly correlated with greater impact. Perennials, reproducing only vegetatively and invading aquatic or riparian habitats were associated with greater biocontrol impact. Our findings could facilitate both the prioritization of invasive plants targeted for biocontrol and the selection of suitable biocontrol agent candidates, which should further improve biocontrol project outcomes.

Prioritizing weeds for biological control development in the western USA: adaptation of the Biological Control Target Selection system - Rachel L. Winston; Mark Schwarzländer; Hariet L. Hinz; Paul D. Pratt (BioControl, 2024)
Nonnative invasive plants (weeds) negatively impact native biodiversity, ecosystem services, agriculture, and the economic interests and health of humans. Since 1902, biological weed control has been employed as a cost-effective and sustainable management option for weeds in the USA. However, biological control is not appropriate for all weeds, nor is sufficient funding available to develop biological control for all weed species. Researchers in South Africa recently developed a Biological Control Target Selection (BCTS) system as an objective, transparent, and simple approach to prioritizing weeds as targets for biological control. The system includes multiple attributes pertaining to the: (1) impact and importance of the target weed, (2) likelihood of achieving success, and (3) investment required to develop and implement biological control. Attributes are scored based on available literature, and the overall score for each weed is used to rank species according to their potential to result in successful biological control programs. This paper describes the adaptation of the BCTS for application to weeds in the western USA not already targeted for biological control.

Ecological benefits of integrative weed management of Melaleuca quinquenervia in Big Cypress National Preserve - Melissa C. Smith; Paul Julian; Don DeAngelis; Bo Zhang (BioControl, 2024)

Recent contributions of molecular population genetic and phylogenetic studies to classic biological control of weeds - John Gaskin (BioControl, 2024)

The highs and the lows: a cost benefit analysis of classical weed biocontrol in New Zealand - Simon V. Fowler; Ronny Groenteman; Quentin Paynter (BioControl, 2024)

Economic impact of a classical biological control program: application to Diachasmimorpha longicaudata against Bactrocera dorsalis fruit fly in Kenya - Komi Mensah Agboka; Henri E. Z. Tonnang; Beatrice W. Muriithi; Saliou Niassy; Shepard Ndlela; Elfatih M. Abdel-Rahman; Samira A. Mohamed; Sunday Ekesi (BioControl, 2024)
Classical biological control (CBC) has been exploited as a safer alternative for suppressing the oriental fruit fly, Bactrocera dorsalis, by importing, rearing, and releasing the larval parasitoid, Diachasmimorpha longicaudata . Although D. longicaudata has been released in Kenya through the Africa Fruit Fly Programme, the extent of its dispersal and subsequent economic benefits have not yet been established. This paper models the spatio-temporal dispersal of the parasitoid using the fuzzy cellular automata approaches and estimates the net benefit from each dollar invested in the CBC approach. We calculated the return on investment based on funding into the programme between 2006 and 2015 and the result of the dispersal range of the parasitoid predicted using an artificial intelligence algorithm. The investment yielded a significant net present value of US$42.8 million over the 16 years. Besides, the cost–benefit ratio showed that for every US$1 invested, the return benefit was US$93 , confirming the profitability of the CBC program. The economic gains are significant considering that there is no environmental contamination and possible adverse effects from the CBC intervention. The study findings support investment in biological control strategies for the eco-friendly and area-wide management of B. dorsalis.

Recent post-release evaluations of weed biocontrol programmes in South Africa: a summary of what has been achieved and what can be improved - Iain D. Paterson; Samuel N. Motitsoe; Julie A. Coetzee; Martin P. Hill (BioControl, 2024)
Biocontrol is widely considered an effective management solution for mitigating the negative impacts of invasive alien plants (weeds). Globally, post-release evaluations to assess individual biocontrol programmes are generally lacking and there have been persistent calls within the biocontrol of weeds literature to increase the quantity and quality of post-release evaluation studies. South African biocontrol researchers have prioritised post-release evaluation studies, with a significant proportion of funding dedicated to this purpose. In this study we review post-release evaluations of weed biocontrol programmes in South Africa that have been published in the last ten years, discuss the different ways these evaluations have been conducted, and identify gaps for future research. Post-release evaluations have been conducted at different scales, including physiological changes within individual plants, plant growth parameters, plant population dynamics and landscape level changes. In most cases, the results of these studies indicated that biocontrol has reduced invasions according to these metrics. While the reduction in the invasion is assumed to alleviate negative ecological and socio-economic impacts, this is usually not directly measured. Evaluations of the socio-economic and ecosystem level benefits of biocontrol were limited to just a few examples on aquatic weeds. More studies that investigate the landscape, socio-economic and ecosystem level changes due to biocontrol are required, especially for terrestrial weeds, if the true scale of the benefits provided by biocontrol are to be understood.

A new paradigm: proactive biological control of invasive insect pests - Mark S. Hoddle (BioControl, 2024)
Invasive insect pests are a significant and accelerating threat to agricultural productivity, they degrade wilderness areas, and reduce quality of life in urban zones. Introduction biological control, the introduction, release, and establishment of host-specific efficacious natural enemies, is an effective management tool for permanently suppressing invasive pest populations over vast areas, often to levels that may no longer cause economic or environmental damage. However, introduction biological control programs are reactive: they are only initiated after an invasive pest has established, spread, and is causing damage that requires mitigation. Host specificity and host range testing of natural enemies for use in an introduction biological control program against an invasive pest can take years to complete. During this time, the target pest population continues to increase, invades new areas, and inflicts damage. Proactive biological control research programs identify prior to their establishment pest species that have high invasion potential and are likely to cause economic or environmental damage once established. Natural enemies are selected, screened, and if sufficiently host-specific, approved for release in advance of the anticipated establishment of the target pest. Following detection of the target pest and determination that incipient populations cannot be eradicated, natural enemies already approved for release are liberated into infested areas. This proactive approach to introduction biological control could significantly reduce project development time post-invasion, thereby lessening opportunities for pest populations to build, spread, and cause damage.

Combination of the entomopathogenic fungus Beauveria bassiana and the plant compound eugenol against the Rhipicephalus microplus tick: mortality, morphological alterations and ovarian lipid profile - Julie Rhanna Tavares Ferreira; Ricardo de Oliveira Barbosa Bitencourt; Isabele da Costa Angelo; Luis Antônio Scalabrin Tondo; Pamella Pryscila de Alvarenga Bisso Lima; Patricia Silva Golo; Renata da Silva Matos; Daniel Guimarães Ubiali; Vânia Rita Elias Pinheiro Bittencourt (BioControl, 2024)

Ecology and management of the coffee berry borer (Hypothenemus hampei): the potential of biological control - Natalia Moreno-Ramirez; Felix J. J. A. Bianchi; Maria R. Manzano; Marcel Dicke (BioControl, 2024)
Coffee is an important commodity in Latin America that is grown by smallholder farmers and large-scale coffee producers. The coffee berry borer, Hypothenemus hampei Ferrari (Coleoptera: Curculionidae: Scolytinae) is a major pest of coffee that originates from West Africa and has invaded all coffee-producing regions. With climate change, the problems that this beetle poses to coffee production are expected to increase. Controlling this pest is a true challenge and chemical insecticides still are one of the main tools used, despite the environmental and human-health issues associated with this approach. To find sustainable alternatives for chemical control of the coffee berry borer, classical biological control, augmentative biological control, and integrated pest management have received extensive attention. Parasitoids, predators, entomopathogenic fungi, and nematodes have been identified and studied for their potential to manage the infestations of this major coffee pest. Conservation biological control has recently gained more attention, but its development is still in its infancy. In this review, we examine strategies for the control of the coffee berry borer in Latin America. We identify knowledge gaps for developing sustainable biological control programs, including conservation biological control within the context of farming systems, land use in the surrounding landscape, as well as the vision of coffee growers.

Niche partitioning association of fungal genera correlated with lower Fusarium and fumonisin-B1 levels in maize - Bwalya Katati; Anne D. van Diepeningen; Henry Njapau; Paul W. Kachapulula; Bas J. Zwaan; Sijmen E. Schoustra (BioControl, 2024)
Through partitioning of ecological niches, several fungi are able to coexist on the same host crop. In (partial) absence of niche partitioning, competitive exclusion among fungi can occur. Competitive exclusion is one of the bases for biocontrol. We investigated fungal correlations, in terms of relative abundance of the fungi, in pre-harvest maize, as a natural ecosystem model. Internal mycobiome fungal relative abundance of maize was used to establish correlations. The maize had been harvested from dry and wet agro-ecological zones of Zambia. The relative abundances of the fungal genera were determined using DNA amplicon sequencing. For this study, positive or absence of correlations between fungal genera signified good niche partitioning (co-existence), whereas negative correlations signified poor niche partitioning and potential for competitive exclusion. When species compete within one niche (competitive exclusion), we may expect to detect higher levels of mycotoxins—since mycotoxins are considered antagonistic agents aimed at defending or invading an ecological niche. To estimate the importance of mycotoxins in competitive exclusion, we measured the influence of the fungal correlations on levels of fumonisin-B1 (FB1) in the maize. FB1 data were derived from a previous study on the maize, determined by HPLC. Results showed that Sarocladium and Stenocarpella had the strongest significant negative correlation with Fusarium , suggesting poor niche partitioning and potential for antagonism of these genera with Fusarium . Furthermore, higher levels of Stenocarpella resonated with lower levels of FB1 and vice versa. It was also observed that, when Sarocladium was in low abundance ( 100 µg kg −1 ) in the pre-harvest maize was highest.

Cold tolerance of the mealybug parasitoid Anagyrus vladimiri - Florence Gilliéron; Jörg Romeis; Jana Collatz (BioControl, 2024)
We investigated the lower thermal limits of Anagyrus vladimiri Triapitsyn (Hymenoptera: Encyrtidae), a natural enemy of mealybugs. Parasitoids were cooled to measure supercooling points and the lower lethal temperature LLT 50 . To investigate survival after long-term cold exposure, parasitoid adults and eggs, larvae, and pupae within their host mummy were gradually acclimated. Adults were then exposed for three days to 7 °C, 5 °C, 3 °C, and 1 °C, and immatures for varying durations to 5, 1, and − 4 °C. Parasitoids were investigated for survival and reproduction. To assess the impact of fluctuating temperature, parasitoid pupae were subjected to daily warming to 10 °C from baseline temperatures of 5 °C, 1 °C, and − 4 °C during four-day-cold exposure. Finally, eggs, pupae and adults were exposed to winter conditions in Switzerland in a semi-field setup. The LLT 50 was − 17.24 °C for adults and 0.94 °C for pupae. Both values were above the supercooling points. No adult survived three days at 3 °C and lower. Likewise, no emergence occurred from eggs or larvae exposed for four days and longer to 1 °C or seven days to 5 °C. Pupae were cold-hardier surviving seven days at 5 °C and three days at 1 °C. Parasitoids surviving cold exposure were still able to reproduce. Daily warming decreased emergence of cold exposed pupae at a baseline temperature of 1 °C but not at 5 °C and − 4 °C. No eggs, pupae and adults survived winter conditions in the semi-field experiment. We thus consider A. vladimiri a chill-susceptible species with very limited cold-tolerance of the investigated population and low chances of survival during winter in Northern Switzerland.

Production improvement and photoprotection of melanin produced by Bacillus thuringiensis - Baoju An; Yunda Zhan; Qian Cheng; Jun Cai; Xiaofei Gu (BioControl, 2024)

Seasonal changes in aphid hyperparasitoid occurrence in sweet pepper and raspberry in Belgium - Francine A. C. van Neerbos; A. Alhmedi; L. Van Herck; E. Van Erkel; R. M. J. De Vis; R. Clymans; T. Beliën; H. Jacquemyn; B. Lievens (BioControl, 2024)

Prey killing rate of a generalist predator may be enhanced by macronutrient manipulation - Søren Toft; Constança Albuquerque; Nina Degn; Hjalte Kjærby; Sarah Kyneb (BioControl, 2024)
Generalist arthropod predators forage not only to gain energy and nutrients, but also to obtain a balanced intake of macronutrients (the intake target). We test two opposite hypotheses concerning the predation rate of nutritionally imbalanced predators: It will increase (1) if the prey is rich in macronutrients that the predator is short of, or (2) if the prey is low in macronutrients that the predator is short of. We used the wolf spider Pardosa amentata (Clerck) as the predator and nutritionally manipulated Drosophila melanogaster Meigen as prey. We completed a full factorial experiment with eight treatment groups, in which we measured predation, consumption and prey utilization of high-protein (HP) and high-lipid (HL) flies by spiders that were previously treated with either HP- or HL-flies for two or six days. The results supported hypothesis 2. Whether spiders had been previously fed HP-or HL-flies, those that were tested against the same type of fly killed more than those tested against the opposite type of fly. A likely explanation for this result is that the predator will be unable to reach its macronutritional intake target by continued feeding on the same prey. It will stay nutritionally imbalanced and continue to catch prey in an attempt to redress its imbalance. In natural systems, predation rates may thus be increased by the widespread mismatch between predators’ nutritional demands and what is available in prey. In practical biological control, it suggests a beneficial effect of feeding the predator prior to release with the pest it is intended to control.

Interspecific competition and comparative cold tolerance in two egg parasitoids of sunn pest, Eurygaster integriceps - Shahzad Iranipour; J. P. Michaud; M. Najafipour; S. Khaghaninia (BioControl, 2024)

Entomopathogenic nematodes to control the hibiscus bud weevil Anthonomus testaceosquamosus (Coleoptera: Curculionidae), above ground and on soil surface - German Vargas; Yisell Velazquez-Hernandez; A. Daniel Greene; Xiangbing Yang; Alexandra M. Revynthi (BioControl, 2024)

Efficacy of a mirid predator and an eulophid parasitoid to the tomato potato psyllid Bactericera cockerelli control on pepper plants - Alejandro O. Guzmán-Pedraza; Ana Mabel Martínez; Ángel Rebollar-Alviter; Luis J. Palma-Castillo; Sinue I. Morales-Alonso; Juan M. Chavarrieta-Yáñez; José I. Figueroa; Samuel Pineda (BioControl, 2024)

Integration of inherited sterility and inoculative releases of a miridae predator for the control of the tomato leaf miner, Tuta absoluta - Lucas Candás; Cynthia L. Cagnotti; Silvia N. López (BioControl, 2024)

Silage pathogens and biological control agents: effects, action mechanisms, challenges and prospects - Huifang Jiang; Charles Obinwanne Okoye; Yanfang Wu; Lu Gao; Xia Li; Yongli Wang; Jianxiong Jiang (BioControl, 2024)

Two insecticidal neurotoxins from parasitoid wasp Habrobracon hebetor venom and their potential use in biocontrol - Sergey A. Timofeev; Anastasia G. Shukhalova; Igor V. Senderskiy; Galina V. Mitina; Philipp B. Gannibal; Viacheslav V. Dolgikh (BioControl, 2024)

Olfactory responses of Nesidiocoris tenuis to uninfested or conspecific-infested banker plants and Thrips palmi-infested eggplants - Kinuyo Yoneya; Satsuki Nishimori; Eizi Yano; Kei Yamaguchi; Matsuri Tsumoto; Rika Ozawa; Junji Takabayashi; Ikuo Kandori (BioControl, 2024)

Laboratory evaluation of a scarabid-specific isolate of Bacillus thuringiensis against white grub Holotrichia serrata - J. Srikanth; B. Singaravelu; N. Crickmore; P. Mahesh; C. Sankaranarayanan; G. S. Suresha; C. Appunu; R. Nirmala; M. Om Prakash; K. M. Athira (BioControl, 2024)

Biological enhancement of the cover crop Phacelia tanacetifolia (Boraginaceae) with the nematophagous fungus Pochonia chlamydosporia to control the root-knot nematode Meloidogyne hapla in a succeeding tomato plant - Jana Uthoff; Desiree Jakobs-Schönwandt; Jan Henrik Schmidt; Johannes Hallmann; Karl-Josef Dietz; Anant Patel (BioControl, 2024)
Root-knot nematodes cause global economic losses in a wide range of crops. We investigated the potential of seed coatings of the cover crop Phacelia tanacetifolia (Boraginaceae) when inoculated with the nematophagous fungus Pochonia chlamydosporia (Hypocreales: Clavicipitaceae) to protect subsequently grown tomato plants from root galling caused by the root-knot nematode Meloidogyne hapla (Tylenchida: Meloidogynidae). Therefore, seeds of P. tanacetifolia were coated with P. chlamydosporia blastospores and planted in M. hapla -infested pots. After 50 days of growth in infested soil, M. hapla eggs were extracted from P. tanacetifolia roots and quantified. Tomato plants grown in the remaining soil served as bioindicator of M. hapla infestation as expressed by the gall index. Results showed that seed coating of P. tanacetifolia with P. chlamydosporia (290 ± 51 CFU per seed) reduced the number of M. hapla eggs up to 95.6% in comparison to untreated controls. Pochonia chlamydosporia as blastospore suspension (5·10 8 blastospores per 600 ml soil) reduced the number of M. hapla eggs by up to 75.5%. Additionally, tomato plants grown for 50 days in substrates previously planted with P. tanacetifolia seeds coated with P. chlamydosporia showed a significantly lower gall index than plants grown in untreated pots. In conclusion, biological enhancement of P. tanacetifolia by seed coating with P. chlamydosporia successfully reduced M. hapla and thus provides an additional tool in the management of this nematode. The method still has potential for further improvement such as increasing blastospore viability within the seed coating by optimized formulation technology.